Prevalence of serum antibodies to Coxiella burnetii in Alaska Native Persons from the Pribilof Islands. (8th November 2019) - Kersh, Gilbert J.; Fitzpatrick, Kelly; Pletnikoff, Karen; Brubaker, Michael; Bruce, Michael; Parkinson, Alan
Abstract: Background: Q fever is a febrile illness caused by infection with the bacterium Coxiella burnetii . It is most often transmitted by inhalation of the bacteria after it is shed by infected livestock. Recent studies have found very high C. burnetii infection rates among marine mammals, but it is not known if shedding by marine mammals creates a risk of Q fever among humans. To better understand infection of humans with exposure to marine mammals, the prevalence of antibodies against C. burnetii in serum samples taken from Alaskan Native persons residing on the Pribilof Islands was evaluated. The Pribilof Islands support large populations of northern fur seals infected with C. burnetii that may increase the risk of exposure for island residents. Methods: Serum testing for IgG antibodies against C. burnetii (phase I and phase II) was performed, and demographic data were analysed utilizing banked serum specimens drawn from island residents from 1980 to 2000. Results: The overall seroprevalence rate was 11.6% (95% CI = 9.3%–14.4%; 72/621). This is higher than the previously reported 3.1% (95% CI = 2.1%–4.3%) seroprevalence for the U.S. population. Conclusions: These results suggest that Alaskan Native persons may be at higher risk for exposure to C. burnetii than the general US. population, possibly due to proximity to large populations of infected marine mammals.